2020
DOI: 10.1159/000507806
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid and High-Sensitivity C-Reactive Protein as Predictors of Cognitive Impairment in Patients with Cerebral Infarction

Abstract: <b><i>Background:</i></b> Cognitive impairment induced by cerebral infarction has become a devastating health problem. More efficient predictors are required to evaluate the potential cognitive decline after cerebral infarction in clinic. Serum uric acid (UA) and high-sensitivity C-reactive protein (hs-CRP) are two factors reported to correlate with cognitive impairment. However, the understanding on serum UA and hs-CRP with cognitive dysfunction remains unclear. <b><i>Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Evaluation of cognitive function after AIS was performed during the hospitalization in six studies 20 22 24 25 26 27 , and during follow-up after discharge in the other five studies 21 23 28 29 30 . Diagnosis of PSCI was based on the Mini-mental State Examination (MMSE) in two studies 20 28 , the Montreal Cognitive Assessment (MoCA) in seven studies 21 22 24 25 26 29 30 , and MMSE or MoCA in one study 27 . The other study reported two datasets of serum UA values for PSCI diagnosed with MMSE and MoCA, separately 23 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Evaluation of cognitive function after AIS was performed during the hospitalization in six studies 20 22 24 25 26 27 , and during follow-up after discharge in the other five studies 21 23 28 29 30 . Diagnosis of PSCI was based on the Mini-mental State Examination (MMSE) in two studies 20 28 , the Montreal Cognitive Assessment (MoCA) in seven studies 21 22 24 25 26 29 30 , and MMSE or MoCA in one study 27 . The other study reported two datasets of serum UA values for PSCI diagnosed with MMSE and MoCA, separately 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Five studies 25 26 27 29 30 with 2679 patients with AIS reported the risk of PSCI comparing between AIS patients with higher versus lower serum UA at admission. Pooled results showed that higher serum UA was associated with PSCI in patients with AIS (OR: 1.33, 95% CI: 1.02 to 1.73, p=0.04; I 2 =72%; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 41 CRP is an acute hepatic biomarker in systemic inflammation correlated with cognitive function. 42 It also demonstrated that higher concentrations of hs-CRP in patients led to cognitive dysfunction after cerebral infarction. 42 Therefore, it could be a potential clinical biomarker to evaluate the level of cognitive decline.…”
Section: Discussionmentioning
confidence: 98%